2018
DOI: 10.1038/s41388-018-0540-5
|View full text |Cite
|
Sign up to set email alerts
|

Communication of prostate cancer cells with bone cells via extracellular vesicle RNA; a potential mechanism of metastasis

Abstract: The role of extracellular vesicles (EVs) as vehicles for cell-to-cell communication between a tumour and its environment is a relatively new concept. The hypothesis that EVs may be critical in co-opting tissues by tumours to generate distant metastatic niches is particularly pertinent to prostate cancer (PCa), where metastatic-tropism to bone predominates over other tissue types. The potential role of EVs as a means of communication between PCa cells and cells of the bone stroma such as osteoblasts, is yet to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 43 publications
3
60
0
Order By: Relevance
“…The increased secretion of growth factors by prostate tumor cells may promote recruitment, proliferation, and differentiation of osteoprogenitor cells, leading to osteoblastic metastasis [67]. Tumor-entrained pre-osteoblasts were shown to promote prostate cancer cells growth in a non-contact co-culture system [104]. For breast cancer, our work demonstrated that osteogenic cells form a growth supportive niche for ERα + breast cancer cells in early stage of bone metastasis [62,66].…”
Section: Metastatic Bone Marrow Nichesmentioning
confidence: 72%
“…The increased secretion of growth factors by prostate tumor cells may promote recruitment, proliferation, and differentiation of osteoprogenitor cells, leading to osteoblastic metastasis [67]. Tumor-entrained pre-osteoblasts were shown to promote prostate cancer cells growth in a non-contact co-culture system [104]. For breast cancer, our work demonstrated that osteogenic cells form a growth supportive niche for ERα + breast cancer cells in early stage of bone metastasis [62,66].…”
Section: Metastatic Bone Marrow Nichesmentioning
confidence: 72%
“…By using techniques to track RNA, the authors also identified the delivery of a set of PCa-RNAs to osteoblast via EVs, which affected their endogenous transcript abundance. This group showed the contribution of the RNA component of EV cargo, providing evidence to support EV communication via RNA molecules as a potential strategy for mediating bone metastasis [ 67 ].…”
Section: Bone Metastasis and Evsmentioning
confidence: 99%
“…This study, as well as other studies, shows the biomarker potential of plasma-derived EV-RNA and the advantages with respect to the cost, ease of workflow and likelihood that all (heterogeneous) tumors are represented by a specific EV population. Communication between a tumor and its environment in PCa via extracellular vesicle (EV) RNAs is a potential mechanism of bone metastasis [63]. It has been shown that exosomal miR-375 significantly promoted osteoblast activity [64].…”
Section: The Potential Of Exosomes In Prostate Cancer Diagnosis and Mmentioning
confidence: 99%